2014
DOI: 10.1038/nmat4157
|View full text |Cite
|
Sign up to set email alerts
|

Light-triggered in vivo activation of adhesive peptides regulates cell adhesion, inflammation and vascularization of biomaterials

Abstract: Materials engineered to elicit targeted cellular responses in regenerative medicine must display bioligands with precise spatial and temporal control. Although materials with temporally regulated presentation of bioadhesive ligands using external triggers, such as light and electric fields, have been recently realized for cells in culture, the impact of in vivo temporal ligand presentation on cell-material responses is unknown. Here, we present a general strategy to temporally and spatially control the in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
386
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(395 citation statements)
references
References 33 publications
4
386
5
Order By: Relevance
“…[5][6][7] Studies using this approach revealed that the time point of cell exposure to adhesion ligands and their density signifi cantly infl uences cell differentiation [ 8 ] and guides vascularization in vivo. [ 9 ] This shows that cells keep track of their adhesion history and that dynamic changes in adhesion signals are imperative in controlling cell functions.…”
Section: Doi: 101002/adma201504394mentioning
confidence: 99%
“…[5][6][7] Studies using this approach revealed that the time point of cell exposure to adhesion ligands and their density signifi cantly infl uences cell differentiation [ 8 ] and guides vascularization in vivo. [ 9 ] This shows that cells keep track of their adhesion history and that dynamic changes in adhesion signals are imperative in controlling cell functions.…”
Section: Doi: 101002/adma201504394mentioning
confidence: 99%
“…Poly(ethylene glycol) di-acrylate hydrogels functionalized with the bioactive RGD peptide sequence have been designed with a photolabile capping blocking the RGD peptide until released by a transdermal UV trigger. [72] This transdermal UV trigger system used lower energy 350-365 nm light, which was able to achieve transdermal activation without detectable harm to murine skin in vivo. [72] However, penetration depth is still a concern [72] and, as is common with photostimulated systems, is not suited for deep tissue applications.…”
Section: Responsive Hydrogelsmentioning
confidence: 99%
“…Light penetration can be attenuated at many depths and wavelengths; however, there are numerous examples where light has been used to either form materials (73) their properties when implanted (74). Ultrasound is another trigger that can be introduced to disrupt polymer structure and release therapeutics (75,76).…”
Section: From Static To Dynamicmentioning
confidence: 99%